COMPLEXITY OF REHABILITATION AFTER SIMULTANEOUS BILATERAL INSTALLATION OF ENDOPROSTHESIS IN A PATIENT WITH DEVELOPMENTAL HIP DYSPLASIA: CASE REPORT - Pejčić, Vuk; Radovanović, Vukota; Kostić, Milica; Janković, Božidar; Milosavljević, Jovana; Cvetković, Bratislav; Kocić, Mirjana (Acta medicae Medianae, 2025)
The gold standard for the treatment of advanced coxarthrosis is the installation of a total hip endoprosthesis. Degenerative hip disease occurs bilaterally in about 42%. The operation is usually performed first on one hip, and after at least 6 months on the other hip. Rarely, this operation is performed simultaneously on both hips, which represents a more demanding operation as well as rehabilitation. This paper is a case report of a patient with good results of functional recovery after bilateral simultaneous hip arthroplasty, who was followed prospectively from the 5th postoperative day until the end of the 3rd.month after surgery. The patient suffered from secondary bilateral coxarthrosis, which is the result of a developmental disorder of the hips. The good recovery results of this patient with simultaneous bilateral hip arthroplasty can be explained by the selection of a good patient selection for simultaneous bilateral arthroplasty, well-chosen endoprostheses, well-done surgery and timely and adequate rehabilitation.
Keywords: hip arthroplasty, coxarthrosis, developmental hip disorder